Impacts of beel nursery management on the variation of indigenous fish species and its socio-economic profitability: a study in the Dhaka beel, Bangladesh - Islam, KR; Sarker, BS; Nazrul, KMS; Tonny, US; Faruque, MO (International Journal of Natural Sciences, 2012)
A research work was conducted to observe the beel management of the Dhaka beel situated in Tangail district, Bangladesh. Data were collected through questionnaire survey, discussion and interviewing. Dhaka beel is a 13ha semi-enclosed beel brought under the nursery management project in 2010. The beel was stocked with approximately 100000 fish larvae of 4 days old during May to June. After 60 days of proper management the stocked larvae were sampled and 70,000 of fry were obtained. In the studied beel the annual production was 2.4 mt in 2009 where beel nursery management has increased the production to 7.10 mt in 2010 which also included several non-stocked indigenous fish species. Socio-economic conditions of people were also improved where 80% of the people believed that it was true. Beel management has played an important role to minimize the rapid reduction of many important indigenous species through four to five months of management where fishes got the chance of recruitment. Management, guarding, harvesting, and income were equally shared among the group members. Findings of the present study suggest that beel nursery management can be an excellent scope for improvement of fish production and socio-economic status of the adjacent people. International Journal of Natural Sciences (2012), 2(3):76-82 DOI: http://dx.doi.org/10.3329/ijns.v2i3.12136